Integration of UAV-based flight control systems with Omnet++ - Shanthini Sandra Mohan. (2011)
In this report, we propose a novel approach of integrating autonomous UAV-based flight control systems with OMNET++, an open source discrete event simulation environment with modular component based architecture. It can be used for modelling of wired and wireless communication networks.